Factors of competitiveness of higher educational institutions (Путеводитель предпринимателя, 2020)
In article consider theoretical aspects of ensuring competitiveness of higher educational institutions. The review of publications of domestic researchers is carried out, conclusions concerning possibility of increase of competitiveness of higher education institution on the basis of management of its image are drawn.